STRUCTURE AND STRATIGRAPHY OF SARHOTA, BANI NAGAL, DUNGI AND THIL AREAS OF DISTRICT KOTLI, JAMMU AND AZAD KASHMIR - Iqbal, S.; Aadil, N.; Parvez, S. (The Nucleus, 2014)
The study area lies in the adjoining areas of the District Kotli, Azad Kashmir which lies along the eastern limb of the HazaraKashmir Syntaxis in the sub-Himalaya of Pakistan. This is a part of Kashmir fold and thrust belt which is formed after the collision of the Indian and Eurasian plates. The lithostructural mapping of Sarhota, Bani Nagala, Dungi and Thill areas is carried out. The lithostratigraphic units exposed are Hangu of Early Paleocene, Patala of Late Paleocene, Margalla Hill Limestone of Early Eocene, Chorgali of Early Eocene, Kuldana of Late Eocene, Murree of Early Miocene, Chinji, Nagri, Dhok Pathan, Soan of Middle to Late Miocene, Mirpur of Pliocene Formations of and Recent Alluvium of Pleistocene. Structurally, the area is highly deformed. Different folds and faults are mapped. The Gawan syncline, Gawan anticline, Sarda-Sarhota syncline, Mandi syncline and Fagosh anticline are the major folds developed in the area. These are tight to open folds which extend northwest to southeast direction. Different parasitic folds along the limbs of the major folds are developed in the study area. The Riasi Fault or Himalayan Frontal Thrust and Fagosh Fault are two major faults present in the study area. The Riasi Fault separates the Early Miocene Murree Formation and Late Miocene Dhok Pathan Formation. The Fagosh Fault is an intraformational fault which lies in the core of Fagosh anticline. Primary sedimentary structures such as cross bedding, ripple marks, load casts and rip ups are used in determining the facing of the stratigraphic units.